Pengaruh Harga Kualitas Pelayanan dan Digital Marketing Terhadap Kepuasan Konsumen Win’s Spa Hair Dressing Batam Studi - Indah Nurbaiti; Hendri Herman; Lukman Hakim (Asosiasi Ide Bahasa Kepri, 2026)
This research seeks to analyze how price, service quality, and digital marketing influence customer satisfaction at Win’s Spa & Hair Dressing Batam, a service-based business operating in the beauty and body care industry. As consumer lifestyles continue to evolve, businesses in this sector are required to deliver value that aligns with customer expectations. This study applies a quantitative approach using a survey method. Primary data were obtained by distributing questionnaires to 61 customers who have experienced the services offered. The collected data were processed and analyzed using multiple linear regression with the support of SPSS version 22. The findings indicate that both individually and collectively, price, service quality, and digital marketing significantly and positively affect customer satisfaction. Pricing strategies that correspond with perceived service benefits and customers’ financial capabilities contribute to higher satisfaction levels. In addition, delivering high-quality services characterized by responsiveness, professionalism, and attentiveness to customer needs plays a crucial role in enhancing the overall experience. Digital marketing also emerges as an important factor, as it facilitates easy access to information and improves communication between the business and its customers. Furthermore, the Adjusted R Square value of 0.757 suggests that 75.7% of customer satisfaction is explained by these three variables, while the remaining percentage is influenced by other factors not examined in this study. In conclusion, implementing appropriate pricing, maintaining excellent service quality, and optimizing digital marketing strategies are essential to improving customer satisfaction and fostering long-term customer loyalty.